The signification and the importance of management in education - Đurić, Igor R. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Accelerated socio-economic changes taking place in the modern world impose the need for a new and deeper reflection on the meaning and the importance of management in education. The knowledge that the development of management as a scientific field in the most direct way determines the future direction of development of economic organizations, created the necessity to (re)examine the possibility of its application in the field of education. In this sense, one has to particularly emphasize the importance of pedagogical and andragogical aspects of management, which is caused by the knowledge that people today are the most important resource of educational institutions and an important factor in their prosperity.The aim of this paper is to highlight the importance of efficient management of human capital, which most directly determines the development and competitive ability of educational institutions. The results show that the principles on which the management as a scientific discipline is based are becoming more and more acceptable in the field of education, which creates a need for elaborated theoretical and empirical studies.
Keywords: functions of management; education; strategic management; management of human resources; educational management; management